Independent Community Empowerment Program to Address Non-Communicable Disease Problems in Coastal Areas of Pekanbaru City - Herlina; Zulfitri, Reni; Agrina; Arneliwati; Nopriadi; Dwiguna, Stephanie; Aziz, Ari Rahmat; Nurhayati; Hunafa, Zahra (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
The purpose of this community service is to make efforts to prevent the spread of non-communicable diseases.   The formulation of the problem in this study is how to conduct early detection (screening) of health, how to increase the knowledge and ability of the Sri Meranti Village Community in overcoming non-communicable disease health problems, and how to empower the community in overcoming and preventing NCD problems that occur at home or in the neighborhood. The research method used is the prevention method by providing education related to what non-communicable diseases are and how to prevent them. The results obtained were an increase in community knowledge related to non-communicable diseases worth 31.41. It is hoped that this program, which has shown success, can be continued so that the number of non-communicable diseases can decrease in the community.